Active tremor control on human hand tremor test rig model using P+fuzzy logic controller - Jamaludin, Hafiz (2019)
Tremor is the vibration in the sinusoidal orientation that are experienced regularly by Parkinson Disease (PD) patients that disturbs their daily lives. Thus, in PD patients, every action will be hindered by the tremor. Hence, this problem needs to be addressed by making a solution to counter the tremor back to ease their daily lives or routines. One solution that may be used to counter this tremor is by making active tremor control system that uses controllers to reduce the tremor vibration. The controller of Proportional (P) and Fuzzy Logic (FL) are being proposed as the controllers to control the linear voice coil actuator (LVCA) and will later be implemented into a system of hand tremor test rig to study the controllers’ performance in reducing the hand tremor vibration. To find out precisely how hand tremor test rig works in reducing tremor vibration, a LabView system modelling is created to help implement the LVCA and controllers together. The current experimental results have shown the combination of controllers consists of P controllers and two different types of Fuzzy Logic controllers (FLC) that use different set of rules have managed to produce satisfactory performance and significant improvements in reducing the hand tremor vibrations. Thus, this research study is done to prove the combination of controllers (P and FLC) can reduce the tremor vibrations better compared to the use of single controllers. Besides that, this research is also done to compare the performance of controllers in terms of its displacement, acceleration, frequency and power spectral density (PSD) values. From this research study, it can be concluded that the most optimum controller that produces the most tremor reduction is the P+FLC 1st set of rules compared to P+FLC 2nd set of rules and P controller only with a highest percentage of 88.39% of tremor reduction with the actual tremor vibrations of PD patients as the reference result. The P+FLC 2nd set of rules has the highest percentage of tremor reduction with a value of 86.81% whereas P controller only has the highest tremor reduction percentage of 67.10%. This percentage of tremor reduction is based on the PSD values in which it represents the intensity of the tremor vibration itself. This experimental study can be used as the initial step for researchers and engineers to design and develop an antitremor device in the future.